+0  
 
0
237
1
avatar

\(\epsilon \)(xi – x)2 where xi = 1, 2, 3, 4, 5

Guest Sep 24, 2017
 #1
avatar+92624 
+1

(xi – x)2 where xi = 1, 2, 3, 4, 5

 

Mmm

Do you mean

 

\(\displaystyle\sum_{\xi=1}^5\;(\xi-5)^2\quad?\)

 

 

\(\displaystyle\sum_{\xi=1}^5\;(\xi-5)^2\\ =(1-5)^2+(2-5)^2+(3-5)^2+(4-5)^2+(5-5)^2\\ =16+9+4+1+0\\ =30\)

Melody  Sep 24, 2017

13 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.